Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Terhadap Kinerja Perusahaan dengan Biaya Keagenan dan Ukuran Perusahaan Sebagai Variabel Moderasi - Resa Dafa Wulandari; Suci Khoirio Atiningsih (Universitas Katolik Soegijapranata, Semarang, 2026)
This research aims to analyze the effect of Corporate Social Responsibility (CSR) disclosure on firm performance, with agency costs and firm size as moderating variables. The study focuses on the Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Employing a quantitative research method with secondary data, the information was analyzed using panel data regression through Eviews 13 software. The results demonstrate that CSR disclosure has a significant positive effect on firm performance as measured by Return on Assets (ROA). However, agency costs and firm size were found to be unable to moderate (strengthen or weaken) the relationship between CSR disclosure and firm performance. These findings indicate that commitment to social responsibility is an independent strategic instrument for increasing corporate profitability in the eyes of stakeholders, regardless of the company's scale or internal interest conflict dynamics.